AB0460 Remission After Discontinuation of Abatacept for Good Response: Results from the ORA Registry. (9th June 2015) - Sagez, F.; Ravaud, P.; Afif, N.; Benmansour, A.; Constantin, A.; Dernis, E.; Dougados, M.; Flipo, R.M.; Jamard, B.; Legrand, J.L.; Morel, J.; Redeker, S.; et al.
Abstract : Background: Discontinuation of biologics is sometimes possible in recent-onset rheumatoid arthritis, but has not been evaluated in established rheumatoid arthritis. Objectives: The objective of the study was to determine the proportion of discontinuation of abatacept for remission, characteristics of patients in remission and duration of biologic-free remission. Methods: The ORA registry has included 1024 patients to study tolerance, efficacy, and drug retention of abatacept prospectively for 5 years. 992 patients had at least 1 follow-up visit. The reasons of discontinuation of abatacept are collected in the electronic CRF, as well as the initiation of a new biologic. The charts of patients having discontinued abatacept for remission for more than twelve months without initiation of a new biologic were analyzed. Results: 10 patients (1.0/% of patients) discontinued abatacept for more than 12 months because of persistent remission. The discontinuation of abatacept was related to remission only (n=6 patients), remission and pulmonary infection (n=1), remission and occurrence of a monoclonal gammapathy (n=1) and remission and pregnancy (n=2). The median disease duration of rheumatoid arthritis before abatacept was 6 (1; 21) years. Nine of the 10 patients were positive for rheumatoid factor and/or anti-CCP. The patients had previously received a median of 1.5 (0;4) synthetic DMARDs and 1.5 (0;3) biologics. 7 patients received methotrexate concomitantly to abatacept. Median DAS 28 was 3.9 (2.5; 8.7) before abatacept. Median duration of treatment with abatacept was 25 (8;40) months with a median of 26 (7;42) infusions. The median duration of remission without a new biologic was 29.5 (12; 39) months. No biologic was reinitiated in 6 of the 10 patients, abatacept was reinitiated in 2 patients and tocilizumab was initiated in 2 patients. Conclusions: These results of the ORA registry demonstrate that only 1% of the patients included in the ORA registry discontinued abatacept for persistent remission. These patients had classical seropositive RA (9/10 patients). In this study, this remission was persistent without any new biologic in 6 out of the 10 patients. In half of the patients approximately, the discontinuation was not only related to the efficacy of the treatment but also to adverse event or pregnancy. Such life circumstances may give us the opportunity to try to discontinue abatacept in responders. Disclosure of Interest: None declared